Fathnameh of Azimuddin Thattavi: A Significant Historical and Literary Document of Sindh - Bashindah, Sohaila; Nazir, Muhammad (sourcecoder, 2024)
For centuries, the Sindh region has utilized Persian as its primary language for scholarship, literature, history, and administration. Many writers and poets from Sindh have created influential works in various fields such as science, arts, culture, literature, history, and mysticism. Among these works, "Fathnameh" a Mathnawi by the esteemed poet Seyyed Azimuddin Thattavi, is particularly noteworthy. As the court poet of Mir Fath Ali Khan Talpur, Thattavi documents the conflicts, battles, and events during the Kalhora and Talpur dynasties' rule in Sindh. His first-hand accounts provide a detailed and valuable perspective, enhancing the historical and literary significance of the work. Additionally, Thattavi's poetic style closely follows the traditions of Ferdowsi's Shahnameh, adding further importance to his writing. This article introduces the book and its author, highlights its historical significance, and explores the political and historical context of Sindh. Our goal is to contribute to the preservation and promotion of Sindh's cultural, literary, and historical heritage.